Introduction of Eco-Friendly Finishing Method (YAKISUGI) among the Millennial Generation in Perina Village: Innovation in Unique Furniture Products with High Aesthetic Value - Fahrussiam, Fauzan; Chaerani, Nurul; Lestari, Dini; Musdi, Musdi; Shabrina, Hasyyati; prasetyo, Andrie ridzki (LPPM Universitas Malikussaleh, 2023)
The demand for a diverse range of solid wood products has been steadily increasing. The unique grain patterns inherent to each wood species render solid wood products to possess distinct market segments. Nevertheless, the inherent vulnerabilities of wood as a biomaterial, such as susceptibility to decay, dimensional instability, and low resistance to organisms, necessitate specialized treatment for wood products. One environmentally sustainable treatment methodology, capable of enhancing the aesthetic value of wood, is the yakisugi finishing technique”a method involving the controlled charring of the wood surface. Notably, this technique remains relatively unfamiliar amongst small and medium-sized wood processing enterprises (UMKM) and the millennial generation. Consequently, this engagement initiative assumes significant importance in introducing the yakisugi finishing method to the millennial cohort. The unique visual characteristics of wood, engendered by this technique, hold the potential to serve as a catalyst for innovation in the realm of wooden product development by millennials. The engagement activities primarily encompass instructional modules, comprising theoretical elucidations and practical applications. Participants, affiliated with the youth group 'karang taruna,' have demonstrated appreciable enthusiasm towards the engagement activities that pertain to the yakisugi technique. It is anticipated that novel products will emerge as a result of the application of the yakisugi finishing technique, particularly within the domain of contemporary minimalist furniture products.